Descripción de competencias clave para el desempeño profesional de los egresados de especializaciones de la Universidad de América (2017)
Being competitive is being updated, in particular, to learn from the global transformations in which we are all immersed. Staying with the knowledge acquired through training or experience allows you to maintain a position that gives calm, but that carries the enormous risk of losing everything by not understanding the changes within a system, in this particular case, of an organization [of its environment. , of its human resources...] inherent to new trends that seek to improve and optimize all types of processes to not only maintain but grow.